(untitled) (International journal of medical sciences, 2026)
Relevance. Essential tremor is one of the most common hyperkinetic disorders that debuts in childhood and adolescence. Tremor of the upper extremities leads to impaired writing, reduced academic performance, and social adaptation. Research objective. To evaluate the efficacy and tolerability of propranolol in children and adolescents with essential tremor under dynamic observation. Materials and methods. Sixty children aged 8–17 years with clinically confirmed essential tremor were examined. Patients were divided into two groups: group 1 (n=30) received standard non-drug therapy in combination with propranolol (1–2 mg/kg/day), group 2 (n=30) received standard therapy only. The observation period was 6 months. Efficacy was assessed using a clinical tremor severity scale, functional test results (spiral, writing, posture maintenance), and quality of life indicators. Results. After 6 months of therapy, a 45% reduction in tremor severity was observed in the propranolol group (p < 0.01) and a 15% reduction in the comparison group (p > 0.05). An improvement in functional indicators was observed in 70% of patients in the main group and in 30% in the control group. An improvement in quality of life was reported in 67% of children receiving propranolol. Side effects were mild and did not require discontinuation of the drug. Conclusions. The use of propranolol in children and adolescents with essential tremor provides a significant reduction in the severity of hyperkinesis and an improvement in quality of life with good tolerability of therapy.